6(3n+1)-3(-1+2n)=n+2n

Simple and best practice solution for 6(3n+1)-3(-1+2n)=n+2n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3n+1)-3(-1+2n)=n+2n equation:


Simplifying
6(3n + 1) + -3(-1 + 2n) = n + 2n

Reorder the terms:
6(1 + 3n) + -3(-1 + 2n) = n + 2n
(1 * 6 + 3n * 6) + -3(-1 + 2n) = n + 2n
(6 + 18n) + -3(-1 + 2n) = n + 2n
6 + 18n + (-1 * -3 + 2n * -3) = n + 2n
6 + 18n + (3 + -6n) = n + 2n

Reorder the terms:
6 + 3 + 18n + -6n = n + 2n

Combine like terms: 6 + 3 = 9
9 + 18n + -6n = n + 2n

Combine like terms: 18n + -6n = 12n
9 + 12n = n + 2n

Combine like terms: n + 2n = 3n
9 + 12n = 3n

Solving
9 + 12n = 3n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-3n' to each side of the equation.
9 + 12n + -3n = 3n + -3n

Combine like terms: 12n + -3n = 9n
9 + 9n = 3n + -3n

Combine like terms: 3n + -3n = 0
9 + 9n = 0

Add '-9' to each side of the equation.
9 + -9 + 9n = 0 + -9

Combine like terms: 9 + -9 = 0
0 + 9n = 0 + -9
9n = 0 + -9

Combine like terms: 0 + -9 = -9
9n = -9

Divide each side by '9'.
n = -1

Simplifying
n = -1

See similar equations:

| 6+2s=148-s | | .2+40= | | x+1-12=-9 | | 5p+7=1 | | 5(h-7)=10 | | 3=0.5h(4+6) | | 5y+7=3x-xy | | a=0.5h(4+6) | | x^2-y=-1 | | x^2+y=-1 | | (p^2-4p-3)(p+1)=0 | | 4(x-1)=2(x+3)(2x-3) | | 4q-1=2 | | 5x+8+3x=10x-2x-8 | | 40=5(x+9) | | 2p-3=2 | | 16=8(x+9) | | 2k^2+2k+2=0 | | 3a+8=10 | | 2x^3+3x^2+2=0 | | a+6=3a+1 | | 6400=n*(1.9n) | | 5n+2=8 | | x^2=-16x-32 | | x^2-12x+4=6x-4 | | 5x+6=-2x-5 | | 16x^2-36x-48=0 | | f(x)=2x^2-18 | | 3-4(x-3)+2=10-3(x+2) | | n^2-10n+10=-6 | | 8(x+9)=24 | | 0.025x^2+800x-70000=X |

Equations solver categories